AMC-integrated reconfigurable beamforming folded dipole antenna with parasitic and RF MEMS - Herwansyah, Lago; Mohd Faizal, Jamlos; Soh, Ping J.; Vandenbosch, Guy A. E. (EMW Publishing, 2016)
A beam-reconfigurable printed antenna on an Artificial Magnetic Conductor (AMC) is proposed for navigation and radiolocation applications at a frequency of 9.41 GHz. The AMC is formed based on a periodic Jerusalem cross shaped slot structure and is located in between two substrate layers, close to the radiator. The AMC plane has a bandwidth of 1.95 GHz around the targeted frequency of 9.41 GHz. By integrating micro-electro-mechanical system (MEMS) switches on the folded patches in combination with parasitic elements, a beam steering capability of up to ±58° is achieved with a rear full ground plane. This eliminates the need for a mechanical steering system, which is traditional in the applications targeted. The antenna achieves a high gain of 8.08 dB and 90% efficiency. A good agreement between simulated and measured results is obtained.